(untitled) (Media Kesehatan Masyarakat Indonesia, 2021)
In Indonesia and especially East Java, incidence of Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHF) has been increasing despite various policies to mitigate or curb the burden of DF and DHF. Studies regarding when the dengue incidence rate would increase are essential for more effective policies. This study sought to analyze the relationship of monthly dengue incidence rate with various environmental factors (temperature, humidity, and rainfall) within a 5-year period at Sampang Regency, East Java, Indonesia. A retrospective cross-sectional study was conducted. Dengue incidence rate within a 5-year period from 21 primary healthcare centers and one hospital as well as data on various environmental factors were collected. The data were tabulated and analyzed using the Pearson Correlation Test. Cumulatively, there are 2.298 DF/DHF cases recorded between 2012–2016. Incidence tend to increase every year. Monthly dengue incidence rate increases after approximately three months of humidity and rainfall increase. Dengue incidence has a significant correlation with rainfall (p=0.008; p<0.05) and humidity (p=0.003; p<0.05) but insignificant correlation with minimum (p=0.653; p>0.05), maximum (p=0.999; p>0.05), and average temperature (p=0.823; p>0.05). We hope this result could help policymakers adjust their policies to anticipate dengue incidence after the rise of rainfall and humidity.